Rejuvenating Tasik Widuri, Rawang community space as ecological link towards a sustainable public space / Nur Azlin Shahirah Shafri - Shafri, Nur Azlin Shahirah (2023)
Community landscape also known as public open space which is encompasses space that provided for community as a network to connect with natural surrounding and people. The aim of this study is to rejuvenate Tasik Widuri, Rawang community spaces as ecological link towards sustainable public space that enhance good quality of life among community. Objective of the study is encourage social inclusion by creating a public space, to design a good and safe surrounding, besides preserving the existing habitat and improve the environmental value. This study focuses on the sustainable community spaces that enhance the environment, social and economy to promote the quality of life among the community. In this study, the inventory and analysis process has been conducted direct at the Taman Tasik Widuri. The data collected from the inventory are synthesized to identify the potential area to enhance the value sense of community. Lastly, the final phase of this study will provide a design proposal which is important to forecast the guideline planning and design practice in this study. This study is hoped to provide a guide to landscape architecture public space studies in creating sense of place and lively space towards striving a sustainable public space in community.